Determination Of Sun Protection Factor (SPF) Values Of Water, Ethyl Acetate, And N-Hexane Fractions Of Kepok Banana Flowers (Musa acuminata x M. balbisiana) Using The UV-Vis Spectrophotometry Method - Evi Eriani; Septian Maulid Wicahyo; Tatiana Siska Wardani (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia as a tropical country faces high UV exposure which causes premature skin aging and cancer risk, so it is necessary to have natural sunscreen from antioxidant-rich plants such as kepok banana flowers (Musa acuminata x M. balbisiana). This study aims to determine the Sun Protection Factor (SPF) value and protection category of water, ethyl acetate, and n-hexane fractions of kepok banana flowers. This type of research is descriptive experimental with ethanol maceration method, multilevel fractionation, phytochemical screening, TLC, and UV-Vis spectrophotometry (290-320 nm, Mansur formula).The results showed that the different types of solvents in each fraction influenced the resulting SPF value. The ethyl acetate fraction showed the highest protective activity compared to the other fractions. The SPF values ​​of the kepok banana flower water fraction with concentrations of 60 ppm, 80 ppm, 100 ppm, 120 ppm, and 140 ppm were 4.662; 7.757; 9.055; 11.944; 15.264, respectively, with moderate-ultra protection. The ethyl acetate fraction obtained SPF values ​​of 18.433; 18.968; 19.203; 19.672; 20.203 with ultra protection. The n-hexane fraction obtained SPF values ​​of 1.190; 1.762; 2.278; 3.575; 4.598 with the category of no-moderate protection.. Concludedthat kepok banana flowers have potential as a natural sunscreen agent, where the ethyl acetate and water fractions provide the most optimal sun protection effectiveness (SPF) compared to the n-hexane fraction.